PENGARUH DANA ALOKASI UMUM (DAU) DAN DANA ALOKASI KHUSUS (DAK) TERHADAP BELANJA MODAL PADA PEMERINTAH DAERAH KABUPATEN LEBAK - Raniah; Usep Siswadi; Ana Ima Sofana (The Asia Pacific Journal Of Management Studies, 2024)
Good government cannot be achieved without optimum supervision so as to achieve conditions of mutual supervision that encourage the Government to manage state resources in a transparent and accountable manner. This study aims to analyze the effect of the General Allocation Fund on capital expenditure and the effect of the Special Allocation Fund on capital expenditure. This research uses quantitative methods. The population used in this study were 62 respondents / employees who worked at the Regional Finance and Asset Agency (BKAD) office in Lebak Regency. Sampling using purposive sampling using primary data. Primary data in the study is data in the form of data from the results of questionnaires distributed. The research data were analyzed using multiple linear regression analysis methods with the help of SPSS version.25.The results of this study found that the General Allocation Fund variable partially affects capital expenditure, the Special Allocation Fund variable partially affects capital expenditure. And simultaneously the General Allocation Fund and Special Allocation Fund variables have a positive and significant effect on capital expenditure.